Deuteron induced Tb-155 production, a theranostic isotope for SPECT imaging and auger therapy. (December 2016) - Duchemin, C.; Guertin, A.; Haddad, F.; Michel, N.; Métivier, V.
Abstract: Several terbium isotopes are suited for diagnosis or therapy in nuclear medicine. Tb-155 is of interest for SPECT imaging and/or Auger therapy. High radionuclide purity is mandatory for many applications in medicine. The quantification of the activity of the produced contaminants is therefore as important as that of the radionuclide of interest. The experiments performed at the ARRONAX cyclotron (Nantes, France), using the deuteron beam delivered up to 34 MeV, provide an additional measurement of the excitation function of the Gd-nat(d, x)Tb-155 reaction and of the produced terbium and gadolinium contaminants. In this study, we investigate the achievable yield for each radionuclide produced in natural gadolinium as a function of the deuteron energy. Other reactions are discussed in order to define the production route that could provide Tb-155 with a high yield and a high radionuclide purity. This article aims to improve data for the Gd-nat(d, x) reaction and to optimize the irradiation conditions required to produce Tb-155. Abstract : Highlights: The medical interest of terbium-155. Deuteron induced reactions on natural gadolinium up to 34 MeV. Excitation functions measured with the stacked-foil technique. Comparison with the TALYS code version 1.6. Tb-155 achievable yield and radionuclide purity.